KEPUASAN PEMUSTAKA TERHADAP LAYANAN REFERENSI DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI NUSA TENGGARA TIMUR - Dolu Soro, Yasintha Herlina; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2020)
ABSTRACT Quantitative research with quantitative descriptive methods. Determination of the sample in this study using purposive sampling, where the determination of the sample is carried out using certain considerations as many as 99 respondents.Data collection techniques using observation, questionnaires, and literature study, data processing techniques in this study using the percentage formula. The instrument of data collection is primary data distributed to respondents. Data analysis techniques in this study are simple linear regression analysis, validity, reliability and hypothesis testing. Hypothesis of sig.t arithmetic <(? = 0.05), it can be concluded that the satisfaction of the user gives an influence, the more satisfied the user, the higher the level of utilization of reference services in the Office of Dinas Kearsipan dan Perpustakaans Provinsi Nusa Tenggara Timur. Keywords: Library Satisfaction, Reference Services.